Effects of neostigmine on postoperative neurocognitive dysfunction: a systematic review and meta-analysis - Zhou, Xuelei; Chen, Linlin; Zhao, Li; Mao, Wei; Liu, Xianchun; Zhang, Longyi; Xie, Ying; Li, Linji (Frontiers in Neuroscience, 2025)
IntroductionPostoperative neurocognitive dysfunction (PND) is a common and serious complication following surgery. Neostigmine, an acetylcholinesterase inhibitor commonly administered during anesthesia to reverse residual neuromuscular blockade, has been suggested in recent studies to potentially reduce the incidence of PND. However, findings have been inconsistent across studies. Therefore, this study conducts a systematic review and meta-analysis to evaluate the effect of neostigmine on PND.MethodsWe conducted a comprehensive literature search across multiple databases, including PubMed, EmBase, Web of Science, Cochrane Library, Scopus, SinoMed, and CNKI, to identify all relevant studies for inclusion. We included randomized controlled trials and cohort studies in our analysis. The risk of bias was assessed using the Risk of Bias 2 tool for randomized trials and the ROBINS-I tool for cohort studies.ResultsA total of 11 studies were included in this analysis, consisting of 8 randomized controlled trials and 3 cohort studies. The incidence of PND was significantly lower in the neostigmine group compared to the control group (log(OR): −0.54, 95% CI [−1.04, −0. 05]; OR: 0.58, 95% CI: [0.35, 0.95], p = 0.03, I2 = 81.95%). Sensitivity analysis led to the exclusion of one cohort study. Consequently, the final meta-analysis comprised 10 studies, encompassing a total of 50,881 participants. The results indicate that the incidence of PND was significantly lower in the neostigmine group compared to the control group (log(OR):−0. 27, 95% CI [−0.47, −0. 08]; OR: 0.76, 95% CI: [0.62, 0.91], p = 0.01, I2 = 2.50%). However, Meta-analysis of RCTs and cohort studies showed no significant difference. Subgroup analysis indicated that neostigmine reduced the incidence of delayed neurocognitive recovery (dNCR), but its impact on POD was unclear, with no significant association to nausea and vomiting. These findings suggest that neostigmine may reduce the risk of PND, but caution is needed in interpretation.ConclusionNeostigmine may have a potential positive effect in reducing the incidence of PND. However, no statistical difference was observed when meta-analyses were performed separately for randomized controlled trials (RCTs) and cohort studies. Given the limited number of studies available and the limitations of the current research, further investigation is needed to clarify the impact of neostigmine on PND.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024537647, Identifier CRD42024537647.